Differential patterns of internally generated responses in parkinsonian disorders. (September 2020) - Tjokrowijoto, Priscilla; Ceslis, Amelia; Sullivan, John.D.O.; Adam, Robert; Mellick, George; Silburn, Peter; Robinson, Gail.A.
Abstract: Internally generated responses are centrally affected in parkinsonian disorders. This study investigated the cognitive components crucial for response generation as reflected in performance on verbal and non-verbal fluency tasks, which require voluntary internal generation of multiple responses. Participants with parkinsonian disorders ( N = 58: 29 Parkinson's disease [PD], 22 corticobasal syndrome [CBS], 8 progressive supranuclear palsy [PSP]) and 89 age-matched controls completed baseline cognitive assessments and eight fluency tasks of four types: word, design, gesture, and ideational. We analysed the total number of correct responses generated and error rates (including repetitions and rule breaks) for PD, CBS and Control groups. The small PSP patient group's performance is reported for comparative purposes only. CBS patients were significantly reduced in the number of correct responses generated across all fluency tasks, without incurring significant errors. The only exception was that CBS patients produced a significantly higher number of repetitions on one nonverbal task (design fluency). By contrast, PD patients' generation was reduced on only three fluency tasks (phonemic word, meaningless gesture, conventional idea). However, they also produced a high error rate on four fluency tasks (rule-break errors: phonemic/semantic word; repetitions: semantic word, meaningless gestures). Overall, the pattern of fluency task performance differs between patient groups. Specifically, the quantity of responses generated is differentially and primarily affected in CBS patients, whereas the quality of responses generated is primarily affected in PD patients. This suggests potentially different patterns of performance for parkinsonian disorders and has implications for the cognitive processes crucial for internally-guided response generation. Highlights: The pattern of fluency task performance differs between parkinsonian disorders. PD patients are impaired in the quality of internally-generated responses. CBS patients are reduced in the quantity of responses generated. Fluency task performance informs underlying cognitive processes.